2018
DOI: 10.1182/blood-2017-07-798157
|View full text |Cite
|
Sign up to set email alerts
|

Integrated molecular profiling of juvenile myelomonocytic leukemia

Abstract: Juvenile myelomonocytic leukemia (JMML), a rare and aggressive myelodysplastic/myeloproliferative neoplasm that occurs in infants and during early childhood, is characterized by excessive myelomonocytic cell proliferation. More than 80% of patients harbor germ line and somatic mutations in RAS pathway genes (eg, ,, ,, and ), and previous studies have identified several biomarkers associated with poor prognosis. However, the molecular pathogenesis of 10% to 20% of patients and the relationships among these biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
133
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(141 citation statements)
references
References 42 publications
(45 reference statements)
7
133
1
Order By: Relevance
“…The high methylation group was dominated by cases with PTPN11 mutation, resulting in poor outcome, suggesting RAS-pathway mutation patterns define epigenetic subclasses in JMML [10]. In addition, hinting at possible functional links between Ras activation and methylation classes, some research also reported that DNA hypermethylation was more pronounced when additional mutations in Ras-pathway genes or epigenetic modifier genes were present [10,17]. Furthermore, we have shown that secondary mutations providing additional activation of RAS-signaling and other signaling pathways were frequent in poor-outcome JMML.…”
Section: Discussionmentioning
confidence: 99%
“…The high methylation group was dominated by cases with PTPN11 mutation, resulting in poor outcome, suggesting RAS-pathway mutation patterns define epigenetic subclasses in JMML [10]. In addition, hinting at possible functional links between Ras activation and methylation classes, some research also reported that DNA hypermethylation was more pronounced when additional mutations in Ras-pathway genes or epigenetic modifier genes were present [10,17]. Furthermore, we have shown that secondary mutations providing additional activation of RAS-signaling and other signaling pathways were frequent in poor-outcome JMML.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent somatic mutations in the Casitas B-lineage Lymphoma (CBL) gene, which encodes an E3 ubiquitin ligase and signaling adaptor, occur in myelodysplastic syndromes (MDS) and other myeloid neoplasms (2)(3)(4)(5)(6)(7)(8)(9), including 10-20% of chronic myelomonocytic leukemia (CMML) patients (10,11). In addition, up to 20% of children diagnosed with juvenile myelomonocytic leukemia (JMML) harbor germline CBL mutations (12)(13)(14)(15). The presence of CBL mutations has been associated with poor prognosis (16)(17)(18), and a better understanding of the mechanisms by which CBL mutations promote myeloid disease is needed for the development of new and effective therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The RING domain, which binds E2 ubiquitin ligase proteins, and linker region are both essential for CBL's E3 ubiquitin ligase function. The majority of CBL mutations in myeloid malignancies are predicted to alter the ubiquitin ligase activity of CBL through single amino acid substitutions within the linker region or RING domain (3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), or splice site alterations resulting in exclusion of most amino acids within the RING domain (15,20). Recurrent mutations predicted to affect CBL's signaling adaptor functions are exceptionally rare, implying that oncogenic CBL mutations result in selective loss of CBL's E3 ubiquitin ligase function.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the authors noted that the methylation profile of samples from children who experienced spontaneous resolution of the disease was more similar to healthy leukocytes than to other JMML cases. The Nagoya University generated genome-wide DNA methylation data of samples from 106 children with JMML [71]. Here the unsupervised cluster analysis revealed two rather than three categories of methylation, potentially due to a significantly lower number of cases with monosomy 7 in the cohort.…”
mentioning
confidence: 99%
“…With the advent of technology permitting the genome-wide analysis of CpG methylation three large-scale epigenetic analyses in a total of 312 children with JMML or related myeloproliferative disorders were conducted by investigators in Europe, North America, and Japan [43,70,71]. Confirming and extending the conclusions derived from the preceding candidate gene studies, the EWOG-MDS demonstrated in a cohort of 167 cases that JMML can be subdivided in three characteristic categories with low, intermediate, and high DNA methylation, with the methylation differences being most pronounced in or near CpG islands [43].…”
mentioning
confidence: 99%